Surgery for Malignant Acute Ischemic Stroke: A Narrative Review of the Knowns and Unknowns - Krishnan, Kailash; Hollingworth, Milo; Nguyen, Thanh N.; Kumaria, Ashwin; Kirkman, Matthew A.; Basu, Surajit; Tolias, Christos; Bath, Philip M.; Sprigg, Nikola (Seminars in Neurology, 2023)
Malignant acute ischemic stroke (AIS) is characterized by acute neurological deterioration caused by progressive space-occupying brain edema, often occurring in the first hours to days after symptom onset. Without any treatment, the result is often fatal. Despite advances in treatment for AIS, up to 80% of patients with a large hemispheric stroke or cerebellar stroke are at risk of poor outcome. Decompressive surgery can be life-saving in a subgroup of patients with malignant AIS, but uncertainties exist on patient selection, predictors of malignant infarction, perioperative management, and timing of intervention. Although survivors are left disabled, most agree with the original decision to undergo surgery and would make the same decision again. In this narrative review, we focus on the clinical and radiological predictors of malignant infarction in AIS and outline the technical aspects of decompressive surgery as well as duraplasty and cranioplasty. We discuss the current evidence and recommendations for surgery in AIS, highlighting gaps in knowledge, and suggest directions for future studies.Key Points
Keywords: decompressive hemicraniectomy; ventriculostomy; suboccipital craniectomy; acute stroke; morbidity; mortality; indication for surgery; surgical decompression